2016
DOI: 10.1080/13554794.2016.1237656
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of number transcoding errors of Chinese- versus English-speaking Alzheimer's disease patients

Abstract: Number processing disorder is an acquired deficit in mathematical skills commonly observed in Alzheimer's disease (AD), usually as a consequence of neurological dysfunction. Common impairments include syntactic errors (800012 instead of 8012) and intrusion errors (8 thousand and 12 instead of eight thousand and twelve) in number transcoding tasks. This study aimed to understand the characterization of AD-related number processing disorder within an alphabetic language (English) and ideographical language (Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Studies comparing different languages and AD incidence and prevalence are scarce outside of alphabetic languages. In a study comparing English- to Chinese-speaking AD patients on a number transcoding task [ 120 ], Chinese-speakers had more intrusions in transcoding numbers than the English-speakers with no meaningful differences in syntactic errors, indicating that the difference is not due to differences in executive function among Chinese- and English-speaking AD patients [ 120 ]. Overall, while comparisons in the incidence and prevalence of AD between speakers of different languages indicate important socio-ethnic influences across cultures, more research is needed to fully understand how AD presentation differs between speakers of different languages.…”
Section: Alzheimer’s Disease and Cultural Group Disparitiesmentioning
confidence: 99%
“…Studies comparing different languages and AD incidence and prevalence are scarce outside of alphabetic languages. In a study comparing English- to Chinese-speaking AD patients on a number transcoding task [ 120 ], Chinese-speakers had more intrusions in transcoding numbers than the English-speakers with no meaningful differences in syntactic errors, indicating that the difference is not due to differences in executive function among Chinese- and English-speaking AD patients [ 120 ]. Overall, while comparisons in the incidence and prevalence of AD between speakers of different languages indicate important socio-ethnic influences across cultures, more research is needed to fully understand how AD presentation differs between speakers of different languages.…”
Section: Alzheimer’s Disease and Cultural Group Disparitiesmentioning
confidence: 99%
“…Proios, Weniger & Willmes, 2002). Furthermore, results from a study comparing transcoding performance of Chinese and English speaking Alzheimer patients, reported that Chiense patients made significantly more 'intrusion' errors (mixing letters and numbers, such as 8thousands and 4) compared to English speaking patients (Ting et al, 2016). The author hypothesised that this is due to the alphabetic (mapping from letters to sounds) nature of English (and most western countries) compare to the ideographical (mapping from symbols to ideas or concepts rather than specific sounds or phonemes) nature of Chinese.…”
Section: Interventions For Transcodingmentioning
confidence: 99%